Food-Related Risks: To What Extent Are Married Jordanian Women (Non-Pregnant, Pregnant and Postpartum) Knowledgeable About These Risks and Their Corresponding Practices? - Ola D. Al-Maseimi; Nour A. Elsahoryi; Omar A. Alhaj; Leena Ahmad; Muna M. Abbas; Suzan Zurkieh (Safety)
Food safety is paramount, especially for vulnerable groups like pregnant and postpartum women. In this cross-sectional study, Jordanian women in different maternal states—pregnant, postpartum, and non-pregnant—were examined for their knowledge and habits regarding food safety. An online survey with 350 respondents yielded information on the participants’ opinions about food safety, personal hygiene, food storage, shopping habits, knowledge of cross-contamination, and handling of baby formula. According to the findings, many participants exhibited poor knowledge (53.7–65.2%) and practices (39.4–50%) related to food safety, with no significant differences in whether or not they were pregnant. Sociodemographic characteristics, including age and information sources, impacted postpartum women’s knowledge and practices about food safety. These findings highlight the importance of food safety education and awareness programs, particularly for pregnant and postpartum women, to lower the risk of foodborne infections during this critical period.